The Principles of Plant Placement in the Interior (Journal of Architectural Design, 2023)
Plants are an important element of good design, they make the space more lively, interesting and cozy. There are various types of plants that differ in size and shape, as well as in placement in space. The article considers examples of plants selected for different rooms in accordance with the conditions of their placement.